Green synthesis of renewable dimethyl terephthalate-like monomer from eugenol - Firdaus, Maulidan; Triana Kusumaningsih; Wibowo, Atmanto Heru; Carissa Hertiningtyas (Penerbit Universiti Kebangsaan Malaysia, 2020)
Dimethyl terephthalate, a diester monomer derived from petroleum-based resources, plays important role in the production of polyester such as polyethylene terephthalate (PET), resins for polyester, fibres, and films as well as engineering polymers. High demand on PET together with environmental concerns require to find alternative for renewable monomers urgently whenever or wherever to substitute the exhausting crude oil-based monomers. A simple and highly efficient method to prepare PET analogue monomer, methyl 2-[2-methoxy-4-[3-(2-methoxy-2-oxoethyl)] thiopropyl]phenoxy acetate (4), from renewable eugenol is described. The key step involves successive Williamson etherification, esterification, to be followed by thiol-ene reaction. Remarkably, it turned out that the thiol-ene reaction has proven to be effective in the introduction of the ester group to the olefinic substrate without the use of solvent and initiator leading to diester 4. The technique offered here comprises advantages i.e. excellent yields, mild reaction condition, and easy to perform, thus, provide a sustainable alternative to synthesize diester from eugenol.